Uma história que não tem fim: um estudo sobre a fantasia literária - Marques, Mirane Campos [UNESP] (2015)
This work proposes a revision and delimitation of the fantasy genre that will fundamentally occur through the dialogue with the notions of fairy tales and fantasy as formulated by J. R. R. Tolkien (2013) in his essay On Fairy Stories. In terms of revision, it will be done a comparison between The Lord of the Rings author's theory and the ones by critics such as Manlove (1982, 1990), Laetz and Johnston (2008), Stableford (1990), Attebery (1980, 1990, 1992). Regarding delimitation, it will interest us, particularly, the counterpoint with the marvelous as thought by Todorov (2007). This posture will contribute to fantasy's affirmation as a better lineate and coherent genre, contributing also to the cohesion of the marvelous itself, since it is a broad genre that brings together several heterogeneous works. Thus fantasy will appear as one of marvelous' limits, precisely when the narrative's supernatural elements have what Tolkien calls internal consistency of reality, constituting a Secondary World. Therefore, while in the marvelous it is found an integration (and harmonization) between natural and supernatural, fantasy imply a disjunction between two realities, two worlds. According to this conception, this work proposes a reading of Micahel Ende's The Neverending Story focusing, on the one hand, in the narrative procedures that favor the fantasy construction, and, on the other hand, in the metalinguistic aspect that occupies a central position in the German writer's novel. Therefore, the approach of Ende's work must simultaneously allow the contact between fantasy's theory and literary work as well as foment connections with other narratives with similar procedures (such as The Chronicles of Narnia, The Lord of the Rings, The Silmarillion, Farmer Giles of Ham and the Harry Potter series), consequently contributing to a better definition of the fantasy genre itself